ACE2 CONTRIBUTES TO THE NORMAL REGULATION OF ARTERIAL PRESSURE AND IMMUNITY IN FEMALES OF REPRODUCTIVE AGE. (April 2021) - Colafella, Katrina Mirabito; Vinh, Antony; Tikellis, Chris; Widdop, Robert; Denton, Kate
Abstract : Objective: Hypertension and cardiovascular disease are age and sex dependent. These differences may, in part, be mediated by the depressor/pressor balance of the renin angiotensin system. Here we determined the role of angiotensin converting enzyme 2 (ACE2) in the regulation of arterial pressure in females of reproductive age and investigated whether targeting deficits in ACE2-generated angiotensin (Ang)-(1–7) restores the normal regulation of arterial pressure during pregnancy. Design and method: Mean arterial pressure (MAP) was measured via telemetry in 14 week old wild-type (WT) and ACE2 knockout (ACE2-KO) male mice and WT and ACE2-KO female mice receiving vehicle or the MasR agonist, AVE-0991 (24 ug/kg/min s.c) prior to and during pregnancy. FACS analysis was used to determine circulating immune cell activation and infiltration into kidneys (baseline and Gd18) and placentae (Gd18). Results: Basal MAP was lower in WT females than ACE2-KO females, WT males and ACE2-KO males (91 ± 2 vs 100 ± 1, 98 ± 1 and 102 ± 2 mmHg, respectively; all P < 0.05 vs WT female). In ACE2-KO females, AVE-0991 lowered basal MAP by 5 ± 1 mmHg (P = 0.03). In WT females, MAP decreased during pregnancy reaching a nadir at Gd9 before returning to pre-conception levels during late gestation. In contrast, in ACE2-KO mice, MAP increased significantly during late gestation (P < 0.0001 vs WT) and this effect was prevented by AVE-0991 (P < 0.05 vs vehicle). This effect of AVE-0991 on MAP was due to changes in diastolic rather than systolic arterial pressure. ACE2-KO mice had smaller litters but greater birth/pup weight than WT mice. AVE-0991 normalised litter size and birth/pup weight in ACE2-KO mice to that observed in WT mice. Circulating and renal T-regulatory cells were lower in non-pregnant and pregnant female and male ACE2-KO mice than their WT counterparts. Treatment with AVE-0991 did not alter the proportion of T-regulatory cells. Conclusions: These data indicate that ACE2 plays an important role in the regulation of arterial pressure and immunity in females of reproductive age. A corollary of this is that deficits in ACE2-generated Ang-(1–7) may contribute to an increased risk of hypertension in non-pregnant and pregnant premenopausal females and therefore may be a novel therapeutic target.